The association between global cognitive function and walking capacity in individuals with broad ranges of cognitive and physical function: Are there sex differences? - Wiley, Elise; Noguchi, Kenneth S.; Moncion, Kevin; D’Isabella, Natalie; Shkredova, Daria A.; Fang, Hanna; Richardson, Julie; MacDermid, Joy C.; Rodrigues, Lynden; Roig, Marc; Tang, Ada (Frontiers in Rehabilitation Sciences, 2022)
Introduction: Cognitive function is known to be associated with physical function, where greater walking capacity has been shown to have moderate to strong correlations with global cognitive function and other various domains of cognition in older adults with and without chronic conditions. Biological sex may moderate the relationship between cognitive and physical function, but whether sex differences exist in this association has not been examined in an aging population. The purpose of this study was to examine the associations between global cognitive function (Montreal Cognitive Assessment; MoCA), walking capacity (6-Minute Walk Test distance; 6MWT) and sex in an aging population with broad ranges of cognitive and physical function. Methods: Participants were assessed for global cognitive function (MoCA) and walking capacity (6MWT). Multivariable regression analyses were performed to examine the interaction of sex in the association between MoCA and 6MWT. First, we presented the unadjusted model (Model 1), then the model adjusted for age, history of stroke, and height (Model 2). To determine if there were sex-based differences in the association between global cognitive function and walking capacity, we included sex and an interaction term between sex*6MWT distance in Models 3 and 4. Results: Twenty-three females and 36 males were included in the multivariable regression analyses, respectively. Our sample represented broad ranges of cognitive and physical function levels, where MoCA scores ranged from 13 to 30, and 6MWT distances from 203m to 750m. 6MWT distance was associated with MoCA in models unadjusted (R2=0.17; F(1,56)=11.4; p<0.01) and adjusted for age, stroke history, and height (R2=0.20; F(4,53)=3.2; p=0.02). No interaction with sex was found, but a main effect of sex was observed (R2=0.26; F(5,21)=3.72; p=0.03). When adjusting for age, height and history of stroke, males MoCA scores were 2.9 ± 1.3 less than the mean MoCA scores for females. Discussion: Our findings confirm the positive relationship between cognitive and physical function in older adults. Notably, we also observed superior performance in global cognition among females that was consistent across a broad spectrum of walking capacity.